PENERAPAN MODEL PJBL UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG MATERI KETENTUAN PUASA DI KELAS III SD NEGERI 055981 - Isriana (CV. Arsy Persada Quality, 2024)
elements in shaping students' character and understanding of religious teachings. Fasting is one of the important pillars of Islam and is a form of worship that must be understood and carried out correctly by Muslims. Experience shows that many third-grade elementary school students do not fully understand the provisions of fasting in depth. With PJBL, students not only get theoretical information about fasting, but are also involved in activities that allow them to apply their knowledge in more contextual situations. This Classroom Action Research aims to determine the increase in students' understanding in teaching fasting provisions in third-grade elementary school students of 055981 Beruam by implementing the Project-Based Learning Model (PJBL). These results indicate that the Project-Based Learning Model (PJBL) Activity is able to improve students' understanding of fasting material in third-grade elementary school students of 055981 Beruam, and learning goes well because the level of students' understanding of children's fasting material also increases. This is based on the results of research conducted by researchers achieving good results with a percentage of 80% of third-grade elementary school students of 055981 Beruam increasing their understanding of fasting material. The success of learning carried out using Project Based Learning Model (PJBL) activities is also seen in student involvement and motivation activities, in participating in learning, students who carry out Project Based Learning Model (PJBL) activities total 15 people with a percentage of 100%, carry out Project Based Learning Model (PJBL) activities according to instructions total 13 people with a percentage of 86.7%, carry out Project Based Learning Model (PJBL) activities well without assistance total 13 people with a percentage of 86.7%.